Cognitive control and metacognitive awareness: do they shape academic achievement in university students? - Musullulu, Hande; Garcia-Orza, Javier; Gómez Vázquez, Diana; Garcia-Sanz, Sara (Frontiers in Psychology, 2025)
Cognitive control and metacognition are important processes that significantly influence learning and academic achievement. Cognitive control facilitates goal-directed actions such as planning and monitoring, while metacognition enables individuals to effectively regulate their learning strategies. Although previous research has highlighted the importance of cognitive flexibility, inhibition and metacognitive regulation in academic performance, the interaction among these factors remains understudied. This study examined the relationship between cognitive control, metacognitive awareness (MA) and academic performance, as measured by grade point average (GPA), in university students. Two dimensions of cognitive control, cognitive flexibility and inhibition were measured using the Wisconsin Card Sorting Test (WCST) and the Go/No-Go Task, respectively. Metacognition was assessed through two subscales of the Metacognitive Awareness Inventory: knowledge of cognition and regulation of cognition. A hierarchical regression analysis revealed that cognitive flexibility was significantly related to GPA, with fewer perseverative errors on the WCST associated with higher GPA. Additionally, regulation of cognition, but not knowledge of cognition, explained further variance. Individuals who reported more frequent use of mental strategies to recognize and control their thinking had higher GPAs. Interestingly, a mediational analysis showed that metacognitive skills did not mediate the cognitive flexibility-GPA relationship. These findings emphasize the independent roles of cognitive flexibility and metacognitive regulation in influencing academic performance. Potential of training programs that target both cognitive control and metacognitive skills for the improvement of academic performance should be addressed in future studies.